Improved Latrine Coverage and Associated Factors Among Rural Community in Gicumbi Gistrict, Rwanda - Umubyeyi Muhimpundu Alice; Rutayisire Erigene (Journal of Public Health International, 2022)
This study aimed at determining improved latrine coverage and associated factors among rural community in Gicumbi district. A cross-sectional study was employed using mixed methods with quantitative and qualitative data collection approaches. The quantitative approach of data collection method was conducted and then qualitative approach followed. A structured questionnaire was used to collect quantitative data and Focus Group Discussions (FGDs) was conducted to collect the qualitative data. The study population consists of household heads or their representatives and key informants from the study area of Gicumbi district. For quantitative the total sample size was 236 households while for qualitative data, a total of three FGDs with eight (8) participants was conducted among twenty four (24) rural community members of Gicumbi district. Raw data from the questionnaire were entered into EPI data and transported into SPSS version 22 for analysis. Descriptive statistics was used to tabulate and describe the data. The strengths of the associations were determined with multiple logistic regressions. The results shows that 69.1% of respondents were male, 30.1% were farmers, 16.9% had formal employment while 57.2% completed secondary education. The prevalence of improved latrine in Gicumbi District was 65.3%. Tertiary education was also 4.3 times more likely to have improved compared to those who did not have formal education (AOR=4.3CI: 95%: 1.027-7.032. P=0.005). Respondents with average monthly income Between 50,000 and 100,000 Rwfs are 2.7 times more likely to have improved latrine (AOR=2.7 CI at 95%:1.009-4.120, P=0.022).
Keywords: Latrine Coverage